Antisipasi Tindak Pidana Pencucian Uang Berkaitan Dengan Profesi Notaris dan Pejabat Pembuat Akta Tanah (PPAT) - Elrika, Elrika; Djaja, Benny (LPPM Universitas Ekasakti Padang, 2024)
The mode of Money Laundering Crime (TPPU) that often occurs in Indonesia is by utilizing the role of Notary and PPAT in performing their duties. Notaries and Land Deed Officials (